Analysis of Occupational Risk Factors of Hot Work at PT Industri Kapal Indonesia (Persero) - A. Ferina Herbourina Bonita; Ummu Khaerat Rahmawan; Suci Fajriani S; Rifdah Wardani; Anindya Monika Putri; Danisarah Prilly; A. Suci Setiani Annisa; Yusniar Anggraeny; Roswati Roswati (Jurnal EduHealth, 2026)
Hot work in shipyards is a high-risk activity that can cause fires, explosions, injuries, and health issues due to exposure to dust and welding fumes. This study aims to describe the risk factors of hot work through the implementation of Job Safety Analysis (JSA) and safety patrol activities at PT Industri Kapal Indonesia (Persero). The research employed a qualitative descriptive approach with field observations conducted during the internship period from Agustus 2025 to October 2025. Primary data were collected through direct observation during safety patrols and analyzed using the JSA method to identify potential hazards, assess risks, and formulate appropriate control measures. The results indicate that each stage of hot work welding, cutting, and grinding has specific risks, including fires, burns, respiratory problems, injuries from metal sparks, and fall hazards. Safety patrols identified non-compliances in the field, such as inconsistent use of personal protective equipment (PPE), work areas near flammable materials, and emergency facilities that require improvement. The integration of JSA and safety patrols effectively enhances risk control and strengthens the safety culture while ensuring compliance with SMK3 regulations and hot work permit procedures.